2018
DOI: 10.1177/0093854818806024
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Violent Offending and Violent Victimization Overlap Among a Sample of Chinese Youth and Young Adults

Abstract: Although an increasing number of studies have examined offending and victimization in China, little is known about the extent of the victim–offender overlap and what factors may explain differential tendencies toward offending versus victimization in the Chinese context. To fill this gap and to broaden the empirical base of the current literature on the victim–offender overlap, we examine the association of a number of prominent theoretical constructs with overall violent encounters and role differentiation. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 63 publications
(99 reference statements)
1
18
1
Order By: Relevance
“…For example, Zhao (2018), surveying 3,628 high school students, found that about one-third (32.4%) of the respondents reported property victimization and only 15.2% reported violent victimization in the last year. Focusing on violent victimization, Wang et al (2019) reported that 10.0% of respondents were hit, 9.5% robbed, and 5.6% attacked with a weapon by someone during the 12 months preceding survey. A high prevalence of violent victimization among adolescents was also reported by Ren et al (2017).…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…For example, Zhao (2018), surveying 3,628 high school students, found that about one-third (32.4%) of the respondents reported property victimization and only 15.2% reported violent victimization in the last year. Focusing on violent victimization, Wang et al (2019) reported that 10.0% of respondents were hit, 9.5% robbed, and 5.6% attacked with a weapon by someone during the 12 months preceding survey. A high prevalence of violent victimization among adolescents was also reported by Ren et al (2017).…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…Accordingly, the nonoffending victims should be distinguishable from victim-offenders. Wang et al (2018) find evidence that peer delinquency and activities are related to role differentiation between victims and offenders. Yet, empirical examinations of this topic are not saturated yet.…”
mentioning
confidence: 84%
“…Furthermore, as discussed earlier, there is profound evidence that victims and offenders share many similarities that create the overlap between both (Chan, 2019;Jennings et al, 2012;Mulford et al, 2018;Schreck & Stewart, 2012;Wang et al, 2018). Victimization can be traced back to features that are also responsible for offending.…”
Section: The Current Studymentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, there is a lack of depth and richness in the insights that such studies provide on victimization and offending (Jennings et al, 2012). Thus far, only five empirical studies on the victim-offender overlap have sampled Asian populations, with participants recruited from South Korea, Mainland China, and Hong Kong (Chan, 2019a;Chan & Wong, 2015, 2020Jennings et al, 2011;Wang et al, 2019). Each of these studies either examined a general or violent trend or focused on a specific offending behavior (i.e., school bullying, cyberbullying, and dating violence).…”
Section: Introductionmentioning
confidence: 99%